2005
DOI: 10.1002/cncr.21072
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reliability of computed tomography‐derived primary tumor volume measurement in patients with supraglottic carcinoma

Abstract: Background: According to WHO 2008 guidelines, an important role is designated for cytoplasmic myeloperoxidase (cMPO) as measured by flow cytometry for classifying acute leukemia of myeloid or ambiguous origin (AML or MPAL). However, no threshold with respect to expression level and percentage positive cells is provided. Since the expression of solely cMPO can change the diagnosis from acute lymphoid leukemia into MPAL in the current WHO 2008, a consensus is needed for the cut‐off for cMPO. Methods: In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…The first is the reproducibility of tumor volume measurements. We previously have reported high levels of agreement among the authors in the determination of the volumes of tumor as part of this ACRIN study (1). This is reassuring for decisions concerning the suitability of radiation therapy as a treatment modality for a given tumor in light of the data suggesting quasi-thresholds of volume above which radiation therapy alone is not likely to eradicate disease.…”
Section: Discussionsupporting
confidence: 59%
“…The first is the reproducibility of tumor volume measurements. We previously have reported high levels of agreement among the authors in the determination of the volumes of tumor as part of this ACRIN study (1). This is reassuring for decisions concerning the suitability of radiation therapy as a treatment modality for a given tumor in light of the data suggesting quasi-thresholds of volume above which radiation therapy alone is not likely to eradicate disease.…”
Section: Discussionsupporting
confidence: 59%
“…Similar results were obtained in nasopharyngeal cancers, and a significant decrease in disease-specific survival was found in patients with larger primary TV. Several other studies have demonstrated that TV is an important prognostic factor in patients affected by non-small-cell lung cancers treated with radiation therapy [3,4,6]. T stage, and thus TV, appeared to have no prognostic significance in oesophageal cancer [18].…”
Section: Discussionmentioning
confidence: 92%
“…Tumour volume (TV) has nevertheless been demonstrated to be an independent prognostic factor in head and neck tumours and in lung cancers while its role in hepatocarcinomas, lymphomas and germ cell tumours is still being studied [4][5][6][7][8][9][10][11][12][13]. Several studies have, in fact, shown that macroscopic TV, calculated on the basis of pretreatment computed tomography (CT) scan, can predict local response after radiation therapy in squamous cell carcinoma arising in different subsites of the head and neck.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several studies have reported good interobserver and intraobserver agreement of tumor size measurements (20,21). However, some other studies have demonstrated substantial variation (22,23). They found that in the setting of different reading experiences, FDG metabolic parameters have higher interobserver agreement than size measurements.…”
Section: Discussionmentioning
confidence: 99%